Tripartitioning the Linguistic Roots in the Five Nominals: A Comparative Study of Semitic Languages - Samira Al-Raheb (دراسات في اللغة العربيّة وآدابها)
This paper deals with the question of defining roots in the light of comparisons which show the importance of such comparative studies, taking into consideration phonetic rules.  These rules were used in modern research to establish the originality of a word or lack of it from the etymological point of view. Analysis, linguistic explanation, and comparisons contribute to tracing the morphological syntax of words by tracking changes and transformations that language has witnessed through time. This study is a foundational study of Arabic roots of the five nominals in comparison with Semitic languages. It concludes with the interpretations of a linguistic phenomenon ancient Arab linguists frequently addressed in their works. In composing their lexicons, these linguists used morphological measures and included derivations and diacritics. This research adopts a comparative- analytical approach and focuses on bilingual lexicon making. The research is interested in the description of phonetic, morphological and syntactical relations in the five nominal and in the structures and forms which open Arabic lexicons as well as Acadian, Ugaritian, Phoenician, Aramaic, and Hebrew ones.